Power in a warming world : the new global politics of climate change and the remaking of environmental inequality - Ciplet, David; Roberts, J. Timmons; Khan, Mizanur Rahman (Cambridge, Massachusetts ; London, England : The MIT Press, 2015)
"An examination of shifting global power dynamics in climate change politics, and how this affects our ability to achieve equitable and sustainable climate outcomes."--
Trading a livable world -- Power shift -- Beyond the north-south divide? -- Manufacturing consent -- The politics of adaptation -- The staying power of big fossil -- Society too civil? -- Contesting climate injustice -- Power in a future world -- Linking movements for justice.
Includes bibliographical references (pages 285-317) and index.
Keywords: Climatic changes -- Political aspects; Energy policy; Climatic changes -- Government policy; Global warming -- Political aspects; Environmental justice